Stability of ribbed shells on the elastic foundation - Gavrylenko, G.D.; Matsner, V.I. (Reports of the National Academy of Sciences of Ukraine, 2014)
An approach to the problem of the stability of ribbed cylindrical shells that are on the elastic foundation under the axial loading and internal (or external) pressure is proposed. The results of calculations for the various parameters of the elastic foundation are given.